A aula comunicativa no contexto escolar : entre a tradição e a inovação - Souza, Glauce Rosa Silva de (2007)
The present study seeks to investigate the degree of communicativeness achieved in a given school context which makes use of the communicative approach for the teaching of English as a foreign language. The attempt to develop the four linguistic skills at the school being focused (which is part of a nationwide military system for high school education) required changes, such as a new organization of the classes according to the students level of proficiency in English, the increase in the teaching staff and the use of new materials. The research analyses the extent to which the innovation entailed by the pedagogical proposal has been truly carried out and incorporated by the teachers or whether it merely consists of superficial alterations. To this end, some members of the teaching staff provided the data for analysis by means of questionnaires and interviews and two of them were also object of class observation and more interviews. Ranging from traditional patterns to taskbased language teaching, the study investigates the communicativeness of the classes observed against the teachers responses. Prabhu s four components of the language pedagogy ideational, operational, ideological and managerial provide an adequate theoretical framework which leads to consistent conclusions about the communicative practice in the school context in focus